Effect of consecutive jumping trials on metatarsophalangeal, ankle, and knee biomechanics during take-off and landing - Lam, W.-K.; Jia, S.-W.; Baker, J. S.; Ugbolue, U. C.; Gu, Y.; Sun, W. (European Journal of Sport Science, 2021)
This study examined the differences in single and consecutive jumps on ground reaction forces (GRF) as well as metatarsophalangeal (MTP), ankle and knee kinematics and kinetics during jumping take-off and landing. Eighteen basketball players performed countermovement jumps in both single and consecutive movement sessions. Synchronised force platform and motion capture systems were used to measure biomechanical variables during take-off and landing. Paired t-tests (or Wilcoxon signed-rank tests) were performed to examine any significant differences regarding mean and coefficient of variation in each of the variables tested. A Holm-Bonferroni correction was applied to P-values to control the false discovery rate of 5%. The findings indicated that consecutive jumps had lower jump height, take-off velocity and landing impact. During take-off, consecutive jumps demonstrated larger peak MTP and ankle extension velocities, knee extension moments as well as larger values for ankle and knee power generation; During landing, the consecutive jumps had larger peak MTP flexion angle, joint velocities (MTP, ankle and knee), and peak knee flexion moments and power absorption. Additionally, consecutive jumps had higher within-trial reliability (i.e. smaller CV) for peak MTP flexion angle at landing (P < 0.05), but lower reliability (i.e. higher CV) for peak knee flexion velocity and power absorption at landing. These results suggest that the consecutive jump trials led to distinct movement kinematics and higher loading responses in jump take-off and landing.